Issues in Online Teaching: Elementary Teachers’ Perspectives (Journal of Education and Educational Development, 2022)
The purpose of this study was to identify the main problems elementary teachers face when teaching online. 13 elementary teachers were interviewed and asked to list the main problems they face when teaching online. Their answers were grouped into the following groups: Assessing students; Behaviour; Communication; Engaging students; Incorporating social-emotional learning; Instructions, modelling, demonstrating; Motivating students; Organisation; Parents over or under support; Planning and delivering lessons; Supporting students; and Technology issues. Then, 554 elementary teachers were surveyed using Microsoft Forms. The findings indicated that the four main problems teachers face when teaching online are related to assessing students, engaging students, parents over or under support and technology. When teacher votes were grouped by country, the findings correlated cross-culturally at .92 correlation, indicating a correlation of significance. A secondary aim of the study was to find whether teachers felt as competent in the online teaching environment as they do in the traditional classroom. The survey showed that 55% of teachers did not feel as competent.